Critical reflections on sustainability as an appropriate political framework of development - Rodríguez Martínez, Víctor (2020)
The Sustainable Development and the Sustainable Development Goals, 2030 SDG, do not arise a real way out of the present civilizing crisis, the one that is taking place in more and more academic, social and politics scenarios. Therefore, the sustainable development speech so spread by the international organizations, government, transnational enterprises and some members from the civil society, only reflects a point of view called “appropriate politically”. This is the one promoting a variety of values and postulates inherit from a modern way of thinking aimed at overriding critical conscience of the people in relation to the real causes of that crisis. Among these causes, we can mention the system of the Wild Capitalism and its consequences that come from the exacerbated consumerism and the intensive exploitation of the natural resources. To that effect, beyond the sustainable development and its goals 2030, this sustainable proposal, as a real and independent alternative, aimed at configuring a new global reality on base of healthy and harmonic relations between human beings and, human beings and nature as recognizing themselves as part of it. Because of it, it is very important to unveil the theoretical and conceptual construction of the words “development” and “sustainable development” this through the historical, epistemological and discursive review.